Perspectives on Technical and Vocational Education and Training: Are young people prejudiced against it? (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
In the contemporary workplaces, people must adapt to the dynamics of the market. The Covid-19 pandemic has highlighted this fact as people had to learn new skills, upgrade existing ones, or relocate to new jobs for sustenance. Technical and Vocational Education and Training (TVET), offering quick skilling, up-skilling, and re-skilling opportunities to people, fits in this scenario. However, TVET has a poor image compared to academic pathways, resulting in low TVET enrollment.  A focused-group discussion with students and recent university graduates in Bhutan revealed that while TVET’s image problem exists, the image itself is a composite of other factors. In particular, the young people’s interest in TVET (or lack thereof) is defined by lack of advocacy in schools for TVET, supply-driven TVET with limited choices, and TVET careers accruing poor economic returns to individuals. Thus, effective social marketing and career advice services in schools, adopting a demand-driven approach to TVET development, and entrepreneurship tracks and collaborative efforts to incentivize vocational careers are some recommended interventions.